Mesenchymal Stem Cells: New Players in Retinopathy Therapy - Rajashekhar, Gangaraju (Frontiers in Endocrinology, 2014)
Retinopathies in human and animal models have shown to occur through loss of pericytes resulting in edema formation, excessive immature retinal angiogenesis, and neuronal apoptosis eventually leading to blindness. In recent years, the concept of regenerating terminally differentiated organs with a cell-based therapy has evolved. The cells used in these approaches are diverse and include tissue specific endogenous stem cells, endothelial progenitor (EPC), embryonic stem cells, induced pluripotent stem cells (iPSC) and mesenchymal stem cells (MSC). Recently, MSC derived from the stromal fraction of adipose tissue have been shown to possess pluripotent differentiation potential in vitro. These adipose stromal cells (ASC) have been differentiated in a number of laboratories to osteogenic, myogenic, vascular and adipocytic cell phenotypes. In vivo, ASC have been shown to have functional and phenotypic overlap with pericytes lining microvessels in adipose tissues. Furthermore, these cells either in paracrine mode or physical proximity with endothelial cells, promoted angiogenesis, improved ischemia reperfusion, protected from myocardial infarction and are neuroprotective. Owing to the easy isolation procedure and abundant supply, fat derived ASC are a more preferred source of autologous mesenchymal cells compared to bone marrow MSC. In this review we present evidence that these readily available ASC from minimally invasive liposuction will facilitate translation of ASC research into patients with retinal diseases in the near future.